The Urgency of Learning Media on Mathematics Learning in Schools - Muhammad Iqra Rabbani; Asep Jihad; Juariah Juariah (Gunung Djati Conference Series, 2022)
Learning media is a tool that teachers use to communicate with students so that the information they receive reaches them effectively. The success of the teaching and learning process is heavily influenced by current learning media. The majority of learning media is still conventional, which has an impact on students' motivation to learn mathematics. The goal of this study is to expose people to knowledge on the impact of instructional media on math learning in schools, as well as the benefits of employing instructional media. The reader will be able to study how learning media plays an important part in education and the impact of learning media correctness on mathematics learning in schools as a result of this research. This research takes a qualitative approach, describing and explaining the impact of instructional media on math learning. The method of data collection used in this study was library research. The purpose of this literature review was to gather theoretical material so that researchers could write with a solid theoretical foundation. There is an impact and urgency on achieving learning objectives by using the appropriate learning media to carry out the teaching and learning process